KEMAMPUAN SEL LIMPA NORMAL MENCEGAH TERJADINYA PENYAKIT AUTOIMMUNE PADA MENCIT IL-2Rβ ββ β -/- - Rifa’i, Muhaimin (Jurnal Kedokteran Brawijaya, 2005)
Adoptive transfer is a potentially curative treatment for both inherited and acquired diseases of hematopoietic compartment and organ failure. The aim of this experiment was to know the potency of normal unfractionated spleen cells to prevent pathological autoimmunity in IL-2Rβ-/-mice. Here, we show that the normal unfractionatedspleen cells have a capacity to prevent autoimmune diseases when adoptively transferred to IL-2Rβ-/- mice. Intravenously, and adoptively transferred of normal unfractionated spleen cells (107) to IL-2Rβ-/-mice (3 wks) gave an evidence on preventing the lethal phenotype due to autoimmune disease in IL-2Rβ-/-mice. The donor cells have a capacity to reverse the status of recipient cells from memory to naïve type. In addition, donorcells also have a capacity to regulate the development of granulocyte cells into normal level of homeostasis. These findings suggest that normal unfractionated spleen cells  could in the future be used in clinical settings to cure autoimmune diseases. Keywords :autoimmune, spleen cells, IL-2Rβ-/-, mice